Efecto de estabilizantes sobre el perfil de textura y características sensoriales en gomitas a base de pulpas de papaya y naranjilla - Loor Aveiga, Nayely Michelle (2024)
The objective of this research was to evaluate the effect of the stabilizers agar agar, guar gum and gum arabic on the texture profile and sensory characteristics of papaya and naranjilla pulp-based gummies. A Completely Randomized Block Design (DCA) was used, which is bifactorial AxB, giving a result of six treatments with three repetitions for each one. The factors under study were the types of stabilizers (agar agar, guar gum, gum arabic) and percentages of pulps (40% and 50%). The variables studied in the texture profile were: hardness, cohesiveness, gumminess, elasticity and chewiness. In addition, an analysis of variance (ANOVA) and Tukey test (p<0.05) were performed using the statistical program SPSS29 free version. In the interaction of the treatments, it was obtained that T2 (50% pulp and 0.7% agar agar) and T6 (gum arabic and 50% pulp) presented the best results in the texture profiles: hardness, gumminess and chewiness. On the other hand, agar-agar gum obtained the best value for the chewiness variable (41.09 ± 12.55 N), presenting no differences with guar and arabic gums in relation to the parameters hardness, gumminess and elasticity; guar gum being better for cohesiveness (0.526 ± 0.55 N). Likewise,the percentage of papaya and naranjilla pulp that presented the best performance was 50%, for the same variables gumminess and chewiness, with 40% being the most suitable for cohesiveness. The most accepted treatment according to the sensory evaluation was T2 in the attributes of odor and texture, while color and flavor did not present significant differences between the treatments. Therefore, the addition of 50% papaya and naranjilla pulp added to the incorporation of 0.7% agar-agar gum improved the texture profile of the gummies.